Anthropometric status in children aged 6-36 months, born from intended and unintended pregnancies in vulnerable communities from the Western Cape Province - Holm, Adri (Stellenbosch : Stellenbosch University, 2019)
Thesis (MNutr)--Stellenbosch University, 2019.